PELAKSANAAN TUGAS BADAN PENGELOLAAN KEUANGAN DAERAH PROVINSI DKI JAKARTA TAHUN 2022-2023: Implementation of the Duties of the Regional Financial Management Agency of DKI Jakarta Province in 2022-2023 - Farhan Aryatama; Wiratno (Reformasi Hukum Trisakti, 2024)
The delegation of authority to regions involves the delegation of authority from the central government, as regulated by Law Number 23 of 2014. Jakarta is a special region, and it is governed by its own law under Law Number 29 of 2007 on Regional Financial Management. However, financial management still refers to Government Regulation Number 12 of 2019. Nevertheless, the implementation of these regulations is not always optimal, as seen in the case of the inclusion of hidden budgets in the quarterly reports of DKI Jakarta's APBD 2023, indicating the need for improvement in the responsibility and transparency of BPKD. The formulation of the problem of this article is how the mechanisms and obstacles in DKI Jakarta's regional financial management. Research methods This article uses normative legal methods, uses descriptive research properties, uses secondary data made from primary and secondary laws. Drawing conclusions using the deductive logic method. The results and conclusions of this research are the financial management of DKI Jakarta by BPKD DKI Jakarta in accordance with Government Regulation Number 12 of 2019, and the obstacles in financial management include a lack of qualified human resources and a poorly integrated information system.